PERFORMA AYAM KAMPUNG SUPER YANG DI BERI LEVEL PENAMBAHAN TEPUNG KULIT KAKAO (Theobroma cacao, L.) FERMENTASI DALAM RANSUM - Syafar Abidin Pakaya; srisukmawati Zainudin; Safriyanto Dako (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2019)
This research aims to find out the appearance of free-range chicken fed with the addition og cocoa skin flour (Theobroma cacao L.)fermented in feeds.the design used is a Completely Randomixed Design with four treatmens and four tepetitions. The parameters observed and measured are the amount of feed consumption, body weight gain, and feed conversion. The data analysis used is the analysis of variance. The findings show that addition of famented cocoa skin flour in level 0%, 5%, 10% do not significantly b influence (P0.05) on the feed consumption,body weight gain and the value of feed conversion in free-range chicken. The conlusion is the additional level of fermented cocoa skin flour to the level of 15% does not influence the appearance of free-range chicken